KLF4 prevented angiotensin II‐induced smooth muscle cell senescence by enhancing autophagic activity. (12th May 2022) - Xu, Hongjie; Yu, Manli; Yu, Yongchao; Li, Yang; Yang, Fan; Liu, Yang; Han, Lin; Xu, Zhiyun; Wang, Guokun
Abstract: Background: Vascular aging is an important risk factor for various cardiovascular diseases. Transcription factor krüppel‐like factor 4 (KLF4) could regulate the phenotypic transformation of the vascular smooth muscle cell (VSMC) in the pathogenesis of aortic diseases. The present study aimed to explore the role and mechanism of KLF4 in angiotensin II (Ang II)‐induced VSMC senescence. Methods: The VSMC senescence mouse model was induced by sustained release of Ang II (1.0 μg/kg/min) for 4 weeks. The premature senescent VSMCs were induced by Ang II (0.1 μmol/L) for 72 h. Cellular senescence was measured by senescence‐associated β‐galactosidase (SA‐β‐gal) activity and p53/p16 expression. The autophagic activity was evaluated by autophagic flux and autophagic marker expression. Results: The expression of KLF4 was extremely increased in abdominal aorta tissues after 1‐week Ang II stimulation ( p < .01) but began to decrease in later periods. Decreased expression of KLF4 was also detected in premature senescent VSMCs. Overexpression of KLF4 could enhance the antisenescence ability of VSMCs. Significantly decreased amounts of SA‐β‐gal‐positive cells and lower p53/p16 expression were detected in KLF4‐overexpressing VSMCs ( p < .01). Next, telomerase reverse transcriptase (TERT) was identified as a direct downstream target of KLF4 in VSMCs. Overexpression of KLF4 in VSMCs prevented the decreased expression of TERT under Ang II stimulation condition, which could in turn, contribute to the enhanced autophagic activity, and ultimately to the improved antisenescence ability of VSMCs. Conclusions: Our results demonstrated that overexpression of KLF4 prevented Ang II‐induced VSMC senescence by promoting TERT‐mediated autophagy. These findings provided novel potential targets for the prevention and therapy of vascular aging.